Misrepresentation of Citations: A Case Study of Google Scholar - Khan, Nadim Akhtar; Bhat, Ajra (Journal of Information and Knowledge, 2023)
The current study aims to identify the misrepresented and actual citations in Google Scholar and rank the professionals according to their correct accreditations. The selected Google Scholar profiles were analysed to reveal the misrepresentation of the citation counts based on the wrong indexing of author names. A total of 30 top prolific author profiles from Library and Information Science professionals were selected for this study. The publication and biographical data were gathered from Google Scholar and compared with Web of Science and Scopus to avoid ambiguity. The findings reveal that misrepresenting citations to the author profiles due to the wrong indexing of author names leads to an increased citation count and affects the resultant author ranking.